UVIT observations of UV-Bright stars in four Galactic Globular Clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Kumar, Ranjan; Pradhan, Ananta C.; Parthasarathy, M.; Ojha, Devendra K.; Mohapatra, Abhisek; Murthy, Jayant
Abstract: We have performed photometric analysis of four Galactic globular clusters (GGCs): NGC 4147, NGC 4590, NGC 5053 and NGC 7492 using far-UV and near-UV filters of the Ultraviolet Imaging Telescope (UVIT) on-board AstroSat. With the help of color-magnitude diagrams (CMDs), we have identified ~150 blue horizontal branch stars (BHBs), and ~40 blue straggler stars (BSS) in the four GGCs. We study the temperature and radial distribution of BHBs and BSS for the four GGCs.